The Education Curriculum in The Era of Artificial Intelligence: A Critical Reorientation of Technological Rationality - Ansori, M. Fadlan; Dartim, Dartim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Advances in artificial intelligence (AI) have significantly influenced the direction of educational curriculum development. The use of AI in education is often positioned as a technical solution to improve the effectiveness and efficiency of learning, but this approach risks narrowing the meaning of education when it is not accompanied by ethical and humanistic reflection. This article aims to critically examine the challenges of educational curricula in the era of artificial intelligence and offer a framework for a reflective and transformative reorientation of curricula. This study uses a literature review method with a qualitative-critical approach to various academic sources that discuss the relationship between technology, curriculum, humanistic education, and Islamic educational perspectives. Data analysis was conducted through thematic and interpretive review to identify the dominant trend of technological rationality and its implications for educational goals. The findings show that the integration of artificial intelligence into the curriculum requires an approach that goes beyond technocratic logic. The curriculum needs to be directed to ensure that the use of AI remains within the framework of ethical values, character building, and social responsibility of students. In the context of Indonesia, which has a strong social and religious background, a value-based reorientation of the curriculum is considered important so that technological innovation does not shift the goals of education, which are oriented towards the development of the whole person. Thus, artificial intelligence can be used as a means of supporting civilized education oriented towards social welfare.